Automotive engine repair and rebuilding - Dorries, Elisabeth H. (Today's technician, 2006)
The theory and service of modern automotive engines is at the heart of this new edition. Thoroughly enhanced and updated, this book includes information on variable valve timing systems, hybrid and other advanced technology vehicles. Readers will learn how components are designed and how they function to support engine operation through the help of realistic line drawings and well-structured photographs that engage them in the parts and pieces of today's automotive engines. The newly revised Third Edition includes more engine performance diagnostic information, as well as current NATEF content to help readers adequately prepare for the ASE certification exam in Engine Repair